Research progress on the role of microbiome-immune-neurotransmitter network in post-stroke sleep disorders - Shi, Wanting; Wu, Li; Qin, Qiong; Li, Yanjing; Chen, Wei (Frontiers in Aging Neuroscience, 2025)
Post-stroke sleep disorders, as a significant complication affecting patient rehabilitation, are closely associated with dysregulation of the microbiome-immune-neurotransmitter network. Following stroke, activation of the hypothalamic-pituitary-adrenal axis and sympathetic nervous system triggers intestinal barrier disruption (reduced tight junction proteins and intestinal permeability) along with microbial imbalance (decreased Bifidobacterium and increased Enterobacteriaceae). Reduced short-chain fatty acids and lipopolysaccharide (LPS) translocation exacerbate systemic inflammatory responses and neurotransmitter imbalances (inhibited serotonin synthesis and excitotoxic glutamate production). These changes further disrupt circadian regulation by the hypothalamic suprachiasmatic nucleus, leading to reduced REM sleep and disrupted slow-wave sleep architecture. Future research should prioritize interventional strategies targeting the gut microbiota, such as probiotics, prebiotics, and fecal microbiota transplantation, integrated with multi-omics technologies and neural circuit modulation approaches, to elucidate the spatiotemporal dynamics of the microbiome–immune–neurotransmitter network and provide a theoretical basis for clinical translation. Restoring brain–gut axis homeostasis is expected to improve post-stroke sleep disorders and neurological functional outcomes in patients.